(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Cervical cancer is the fourth most common cancer affecting women worldwide. Immunohistochemical expression of several biomarkers; including those regulating apoptosis and angiogenesis; may help to distinguish reactive conditions from precancerous and cancerous lesions of the uterine cervix. Objective:To assess the IHC expressions of p53, bcl2 and CD34 in cervical intraepithelial neoplasias and carcinomas. Methods:A cross sectional study included a total of 127 formalin-fixed paraffin-embedded cervical tissue blocks; of which 22 cases were chronic cervicitis, 24 cases were low grade squamous intraepithelial lesion (LSIL), 28 cases were high grade squamous intraepithelial lesion (HSIL) and 53) cases were invasive cervical carcinomas. Sections from each block were immunohistochemically stained for p53, bcl2 and CD34. Results: p53 was not expressed in chronic cervicitis, with significant increase in its expression from LSIL through HSIL to carcinomas had been identified. A significantly higher IHC expression of p53 was observed in adenocarcinomas and adenosquamous carcinomas compared to squamous cell carcinomas. Bcl2 was expressed in all cases with non-significant differences. Regarding CD34 IHC expression; there was a significant increase in microvessel density (MVD) from chronic cervicitis through LSIL and HSIL to carcinomas. A significantly higher MVD was detected in adenosquamous carcinomas and adenocarcinomas, in poorly differentiated carcinomas and was significantly increasing with stage. Conclusions: p53 plays an important role in the progression of the severity of intraepithelial cervical lesions. MVD can be utilized as ancillary marker for the risk of malignant transformation of cervical intraepithelial lesion. Key words: LSIL, HSIL cervical carcinoma, p53, bcl2, CD34, MVD